Pain self-efficacy questionnaire and its use in samples with different pain duration time - Bonafé, Fernanda Salloume Sampaio; Marôco, João; Campos, Juliana Alvares Duarte Bonini (Sociedade Brasileira para o Estudo da Dor, 2018)
ABSTRACTBACKGROUND AND OBJECTIVES: The pain self-efficacy questionnaire has been frequently used in several languages, but its use is limited to chronic pain. This study aimed to i) evaluate the properties of the pain self-efficacy questionnaire among Brazilians with different durations of pain occurrence; ii) present a new proposal for estimation of the overall self-efficacy belief score; and iii) compare such score among different pain duration time.METHODS: A total of 1,155 adults (79.0% women; 38.6±10.8 years) participated, 337 had no pain, 386 reported pain for less than 3 months, 253 reported pain for more than 3 months with a recurrent pattern, and 179 reported continuous pain for more than 3 months. The confirmatory factor analysis was performed to check the pain self-efficacy questionnaire unifactorial model good-fit. The pain self-efficacy questionnaire invariance was tested in independent samples using multigroup analysis. We proposed the calculation of the self-efficacy belief score from the factor score obtained in the confirmatory factor analysis. The score was compared among groups (ANOVA, alpha=5%).RESULTS: After inserting four correlations between errors of items, the pain self-efficacy questionnaire model shows to be fit to the sample (X2/df=7.059; CFI=0.978; GFI=0.964; RMSEA=0.072). The model was invariant between independent samples. Lower self-efficacy belief was found among participants with pain for less than three months (p<0.05).CONCLUSION: There is evidence of a relationship between the self-efficacy belief and the pain characteristics, where the presence of pain and length of time living with pain might be important factors in the study of the concepts involved in the perceptions of pain and self-efficacy.

RESUMOJUSTIFICATIVA E OBJETIVOS: A utilização do questionário de autoeficácia relacionado à dor tem sido frequente, porém, limitada ao contexto da dor crônica. Os objetivos deste estudo foram: i) avaliar as propriedades psicométricas do questionário de autoeficácia relacionado à dor para amostra de indivíduos brasileiros com diferentes durações da ocorrência de dor, ii) apresentar uma nova proposta de estimativa do escore global da crença de autoeficácia e iii) comparar esse escore entre grupos com diferentes durações de dor.MÉTODOS: Participaram 1.155 adultos (79,0% mulheres; 38,6±10,8 anos). Do total, 337 não apresentavam dor, 386 relataram dor há menos de 3 meses, 253 relataram dor recorrente há mais de 3 meses e 179, dor contínua há mais de 3 meses. Realizou-se análise fatorial confirmatória para verificar o ajustamento do modelo do Questionário de Autoeficácia relacionado à Dor. A invariância do questionário de autoeficácia relacionado à dor foi testada utilizando análise multigrupos. Foi proposto cômputo do escore global da crença de autoeficácia a partir da matriz dos pesos de regressão da análise fatorial confirmatória. O escore de autoeficácia foi comparado entre grupos (ANOVA, alfa=5%).RESULTADOS: Após inserção de quatro correlações entre os erros dos itens, o modelo do questionário de autoeficácia relacionado à dor apresentou ajustamento adequado à amostra (X2/gl=7,059; CFI=0,978; GFI=0,964; RMSEA=0,072). O modelo foi invariante entre as amostras independentes. Menor escore de crença de autoeficácia foi encontrado entre os participantes com dor presente há menos de 3 meses (p<0,05).CONCLUSÃO: Há evidências da relação entre a crença de autoeficácia e as características da condição dolorosa, o que permite discussões acerca das conceituações teóricas envolvidas na percepção da dor e autoeficácia dos indivíduos.
Questionário de autoeficácia relacionado à dor e seu uso em amostra com diferentes durações de ocorrência de dor
Keywords: Pain; Pain measurement; Psychometrics; Scale; Self-efficacy; Validation; Autoeficácia; Dor; Escala; Mensuração da dor; Psicometria; Validação